THE EFFECTS OF WEBBING TECHNIQUE ON THE FIRST YEAR STUDENTS’ ABILITY IN WRITING DESCRIPTIVE PARAGRAPH AT SMP N 23 PEKANBARU. - Putri, Kiki Reziani; Aruan, Rumiri; ', Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This quasi-experimental research aimed to find out whether there is significant effect of webbing technique on the first year students’ ability in writing descriptive paragraph at SMP N 23 Pekanbaru. The researcher used cluster sampling technique to determine the sample. The samples were 36 students as experimental group and 36 students as control group. Writing test is used to get the data by giving pretest and posttest. In analyzing the data, the researcher used t-test formula. The analysis of the data showed that there was significant effect of webbing technique on the students’ ability in writing descriptive paragraph. The mean score of the students before the treatment was 55.83 in experimental group and 56.58 in control group. The mean score of the students after the treatment was 71.09 in experimental group, while in control group was 66.70. Moreover, from the statistical analysis, it was found out the T-observed (1.83) was higher than T-table at the level of significance 0.05 (1.667). Based on this finding, it is suggested that webbing technique can be used by the teacher as an alternative method in the teaching writing, particularly in descriptive text.Keywords: Webbing Technique, Writing Ability, Descriptive Paragraph